1. ## -7y = 0

I came out with the right answer, but did I work this out correctly?

-7y = 0
-7y/-7 = 0/-7
-y = 0
-y/-y = 0/-y
y=0

2. Originally Posted by Euclid Alexandria
I came out with the right answer, but did I work this out correctly?

-7y = 0
-7y/-7 = 0/-7
-y = 0
-y/-y = 0/-y
y=0
Hello,

you have made only a minor mistake:
-7y/-7 = 0/-7
y = 0

because -7y/-7 = +y the last two lines aren't necessary (and slightly wrong).

Greetings

EB

3. also going from
$\displaystyle -y = 0$
and you then said
$\displaystyle -y/-y = 0/-y$
this is not equivalent to:
$\displaystyle y=0$
as you said.

you had $\displaystyle -y=0$
so what you want to do here to get the solution is divide both sides by $\displaystyle -1$
$\displaystyle -y/-1 = 0/-1$
$\displaystyle y=0$

since it turns out $\displaystyle y=0$
before you were trying to say $\displaystyle -y/-y$ which is $\displaystyle 0/0$ which is undefined.

4. Thanks, guys. I couldn't remember the rule for getting a negative variable to be positive. You always divide both sides by -1?

5. you could either divide by -1, multiply by -1, the effect is the same. you don't tend to think of it as "multiplying/dividing by -1" though. you just change the sign of both sides. for instance if
$\displaystyle -x = -4$
then
$\displaystyle x = 4$
you are simply changing the sign of both sides. you don't really need to explain yourself when doing that
$\displaystyle -y=17$
$\displaystyle y=-17$